Ornithine and arginine decarboxylase activities and effect of some polyamine biosynthesis inhibitors on Gigaspora rosea germinating spores - Sannazzaro, A.I. (2004)
The pathways for putrescine biosynthesis and the effects of polyamine biosynthesis inhibitors on the germination and hyphal development of Gigaspora rosea spores were investigated. Incubation of spores with different radioactive substrates demonstrated that both arginine and ornithine decarboxylase pathways participate in putrescine biosynthesis in G. rosea. Spermidine and spermine were the most abundant polyamines in this fungus. The putrescine biosynthesis inhibitors α-difluoromethylarginine and α-difluoromethylornithine, as well as the spermidine synthase inhibitor cyclohexylamine, slightly decreased polyamine levels. However, only the latter interfered with spore germination. The consequences of the use of putrescine biosynthesis inhibitors for the control of plant pathogenic fungi on the viability of G. rosea spores in soil are discussed. © 2003 Federation of European Microbiological Societies. Published by Elsevier B.V. All rights reserved.